Nutritional Composition and Lipid Oxidation Stability of Beef Patties Packed with Biodegradable and Non-Biodegradable Materials - Ling, Lim Siok (Universiti Sains Malaysia, 2013)
Application of bio-based packaging materials have been shown to prevent moisture loss, reduce lipid oxidation and improve flavor attributes of foods. Biopolymers can be classified according to the method of production or mode of degradation. Properties of biopolymer can be tailored through polymer architecture in order to be comparable to the other synthetic polymers used in food packaging field. Biopolymers can be applied in beef patties packaging which has commercial shelf life of around one to two years as the polymer has a longer service lifetime before degradation occurs. The stability of nutritional composition, lipid oxidation, physical traits of beef patties packed with different types of plastics and the surface morphology of plastics after 3 months of storage were studied. Beef patties were packed with either non-biodegradable high density polyethylene, oxo-biodegradable plastic, hydro-biodegradable low density polyethylene/thermoplastic sago starch plastic or hydro-biodegradable polylactic acid plastic. There were no differences in the trend of changes for all nutrient analyzed and lipid oxidation values of beef patties packed with either biodegradable or non-biodegradable plastics after storage except for ash of raw patties. There were significant (P< 0.05) decreased in fat for cooked patties and moisture for both raw and cooked patties but significant (P< different in ash of raw patties packed with oxo-biodegradable plastic and polylactic acid plastic after storage. Lipid oxidation values of beef patties increased after storage but they were not significant (P > 0.05). Beef patties packed with biodegradable packaging materials were able to retain moisture without jeopardizing the diameter reduction during storage. Only polylactic acid plastic showed some cracks on the surface after storage. In summary, the application of biodegradable plastics packaging for beef patties was considered acceptable and can be improved as most of the changes in nutritional composition, lipid oxidation and physical traits of beef patties after 3 months of storage were comparable with conventional polyethylene plastic packaging.